Teacher Expectations as a Political Issue in Rural Alaska Schools - Judith Kleinfeld; Williamson McDiarmid (Journal of Research in Rural Education, 1986)
To measure teacher expectations for academic achievement in rural Alaska schools, we surveyed 304 randomly selected teachers. Teachers in predominantly Native schools held significantly different views about students' potential educational attainment and achievement than teachers in predominantly Caucasian schools. Fewer teachers in Native communities thought students would attend or graduate from college or could achieve at or above national norms. The debate these findings stimulated indicates the way teacher expectations research has been politicized in rural Alaska. Many rural educators see these beliefs as nothing more than a realistic assessment of present educational conditions and emphasize that these beliefs should not count as "low expectations." Many Native leaders, in contrast, see these attitudes as evidence of what they have always suspectedthe prejudiced attitudes that, in their view, create school failure among Native children. This article discusses the educational problems created by politicized debate on teacher expectations.